The Dynamics of Human Environmental Behaviour: A Behavioural Approach to Nature Conservation Efforts - Ilal Ilham; Aldri Oktanedi (Journal of Sumatera Sociological Indicators, 2024)
ABSTRACT This article examines the dynamics of human environmental behavior through a behavioral approach to nature conservation efforts. The research highlights the importance of pro-environmental behavior, which can be influenced by social norms, economic incentives, and environmental education. By analyzing various studies and successful interventions applied in several regions, such as the recycling program in Surabaya and the "Bye Bye Plastic Bags" movement in Bali, this article demonstrates how behavioral change can support environmental conservation. The behavioral approach, which includes the Theory of Planned Behavior (TPB) and social influence, is considered an effective tool for changing community habits to actively participate in environmental preservation. By utilizing interventions based on social norms, economic incentives, and educational campaigns, this research provides recommendations for more effective behavior-based environmental conservation policies in Indonesia. Keywords: Environmental behavior, social norms, economic incentives, environmental education, nature conservation ABSTRAK Artikel ini mengkaji dinamika perilaku lingkungan manusia melalui pendekatan behavioral dalam upaya pelestarian alam. Penelitian ini menyoroti pentingnya perilaku pro-lingkungan yang dapat dipengaruhi oleh norma sosial, insentif ekonomi, dan pendidikan lingkungan. Dengan menganalisis berbagai studi dan intervensi yang berhasil diterapkan di beberapa daerah, seperti program daur ulang di Surabaya dan gerakan "Bye Bye Plastic Bags" di Bali, artikel ini menunjukkan bagaimana perubahan perilaku dapat mendukung konservasi lingkungan. Pendekatan behavioral, yang mencakup teori perilaku terencana (TPB) dan pengaruh sosial, dianggap sebagai alat yang efektif dalam mengubah kebiasaan masyarakat untuk berpartisipasi lebih aktif dalam pelestarian alam. Dengan menggunakan intervensi berbasis norma sosial, insentif ekonomi, dan kampanye pendidikan, penelitian ini memberikan rekomendasi untuk kebijakan pelestarian lingkungan berbasis perilaku yang lebih efektif di Indonesia. Kata kunci: Perilaku lingkungan, norma sosial, insentif ekonomi, pendidikan lingkungan, pelestarian alam.